The Effects of International Trade on Income Convergence of the European Union Member States - Milutinović, Sonja I (Industrija, 2016)
The income convergence is a subject of debate among economists since the formulation of the Robert Solow’s neoclassical growth model. The income convergence is a situation when income of poorer countries is approaching the income level of richer countries, due to more pronounced economic growth rates of poorer countries in a certain period of time. Faster growth of poorer countries is a consequence of diminishing returns on capital, which is a basic assumption of the neoclassical growth model. The subject of this paper is the effect of international trade on income convergence of the European Union member states. Regression analysis is used in this paper to test the research hypothesis: higher volume of bilateral trade causes income convergence. The results tell us in favour of the proposed hypothesis - higher volume of bilateral trade leads to income convergence.